Souvenir Khas Dayak dari Hasil Hutan Bukan Kayu Getah Nyatoh: Typical Dayak Souvenirs from Nyatoh Non-wood Forest Products - Nuwa, Nuwa; Rotinsulu, Johanna Maria; Triyadi, Antonius; Prihanika, Prihanika (JURNAL HUTAN TROPIKA, 2025)
Palangka Raya City covers an area of ​​2,687 km2, with a 2015 workforce dominated by high school graduates (27.7%) and university graduates (27.2%). High school graduates were the most unemployed at 2%, followed by vocational high school graduates at 1.4%, and then university graduates at 1% of the total workforce in 2015. This aligns with the Vision and Mission outlined in the RPJMD (Regional Medium-Term Development Plan), namely: "To realize a city of Palangka Raya that is Advanced, Harmonious, and Prosperous for All and to realize the welfare of the Palangka Raya community through a smart economy, encompassing the development of industry, small and medium enterprises, tourism, and banking." Palangka Raya's flagship products are rattan, wood, batik, and nyatoh resin crafts, which have significant potential for development, particularly to support the synergistic regional tourism industry. The Dayak people, as the indigenous people of Central Kalimantan, live largely along river basins and depend on the natural resources of their surroundings for their livelihood. Their interaction with nature has given rise to a diverse culture reflecting local wisdom. The objective of this activity is to produce nyatoh sap, a non-timber forest product, into typical Dayak souvenirs, including miniature boats, garing sticks, pen holders, key chains depicting Dayak statues, mandau (mandau), talawang (talawang), and hornbills. This activity, held in the Forestry Department, aims to provide students with an understanding of the types of non-timber forest products made from sap, namely nyatoh sap, as well as an introduction to cleaned and colored nyatoh sap, and the process of forming it into souvenirs.